Development of an oscillating cum rotary disk potato digger - Paramadevan, N.; Gupta, C.P.; Jindal, Vinod Kumar; Bohez, Erik L.J.; Nielsen, J.M. (Bangkok : Asian Institute of Technology, 1991)
Two versions of the tractor mounted oscillating rotary disk potato digger were designed and fabricated at the Asian Institute of Technology. They were the prototype and the modified version. In the prototype version, the solid concave disk was rubber coated to prevent potato bruising and mounted with a spring at its back to provide oscillatory motion due to varying soil resistance. Drive power to rotate the disk was transmitted from the tractor's p.t.o through a series of drive shafts. Fifty-six mm spring and 40 r/min of disk rotation corresponded to maximum amplitude in resonance and minimum draft with soil and yielded tubers free from adhering soil, bruises and cuts. The dual perforated disk used in the modified version were the spider web and bar perforations. The bar perforated disk was coated and the spider web was not coated with rubber. The scraper to deflect soil and potato were also perforated in order to reduce the volume of soil going to the sieve. A spring was also mounted at the back of each perforated disk to provide the oscillatory motion due to varying soil resistance. Rotary power to rotate the disk was provided by the p.t.o of the tractor. It was found that the rubber coated bar perforation yielded less seriously cut tubers than the uncoated spider web perforation.
A thesis submitted in the partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Potato harvesting machinery